The case presentation of a phenytoin related gingival fibromatosis and the review of the related literature - Nóra Tari; Gábor Fábián; Miklós Kaán; István Gera (Hungarian Dental Association, 2019)
The objective of this case presentation is to present a case of a phenytoin associated gingival fibromatosis in a 14 years old girl and the results of its comprehensive periodontal-orthodontic therapy. An attempt was also made to summarize the literature background of the clinical features and mechanism of drug induced gingival overgrowth. The gingival overgrowth is a common side effect, following the long term administration of anticonvulsant drugs, calcium channel blockers, and immunosuppressant drugs (phenytoin, nifedipine, and cyclosporine) to control epilepsy, hypertension, and organ transplant rejection respectively. The pathogenic mechanism has been intensively studied by numerous authors but it is still not totally understood. It is common in the pharmacological action of the three chemically totally different molecules that they suppress the cation channels (Na+, Ca++) in in the fibroblasts that control the active folic acid uptakes. The folic acid has a key role in controlling the MMP enzymes expression by the gingival fibroblast. Nevertheless alteration in the expression of different pro and anti-inflammatory cytokines have also been documented. Those molecules also have a direct stimulatory effect on the gingival fibroblast to synthesize excessive amount of collagen. In the presented case our patient had severe postnatal complications and at the age of three developed epilepsy (grand mal) that was difficult to control and finally at the age of 8 neurologist decided to administer phenytoin. The patient showed up at the Periodontal Department of Semmelweis University at the age of 14 complaining of severe gingival enlargement, speech difficulties and complicated tooth eruption. After initial motivation a series of external and internal bevel gingivectomy as well as apically repositioned flap surgeries were performed to remove the fibrotic gum, to assist permanent tooth eruption and re-establish the normal morphology of the gingiva. Originally patient had an Angle Class II malocclusion but due to the fibrotic gingiva the normal tooth eruption was also severely hampered. The orthodontic therapy was provided by the Department of Pediatric Dentistry and Orthodontics of Semmelweis University. The Angle class two malocclusion and the buccal position of the upper front teeth were corrected with bimaxillary fixed orthodontic appliances and after another three years the than 19 years old patient's periodontal and dental condition as well as her self-esteem has been finally restored.